2021
DOI: 10.1080/08911762.2021.1934770
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Female Shoppers’ Attitude and Purchase Intention toward Green Cosmetics in South Africa

Abstract: This paper investigates female shoppers' attitude and purchase intention towards green cosmetics. Underpinned with an extended theory of planned behaviour model, the research framework examines consumers' attitude and purchase intention. In addition, the moderating influence of consumer involvement is tested. Data (n = 408) were collected from South Africa and analysed through structural equation modelling. The results show that subjective norm has a significant positive impact on the consumers' purchase inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
3
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 120 publications
8
78
3
8
Order By: Relevance
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32]. Another possible explanation for these results is the use of a single-item measurement rather than a validated scale.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32]. Another possible explanation for these results is the use of a single-item measurement rather than a validated scale.…”
Section: Discussioncontrasting
confidence: 99%
“…Literature focusing on green cosmetics and skincare products in particular shows similar results; concerns about the environment and human health predicted a more positive attitude towards green skincare, which in turn predicted purchase intention [21,29,30]. However, some studies report that attitudes toward health and the environment are not strong enough motives to influence consumers' purchase intention and attitudes toward eco-friendlier products [31][32][33].…”
Section: Attitude Knowledge and Behavior In Relation To Green Skincare Productsmentioning
confidence: 81%
See 1 more Smart Citation
“…In a study by Nguyen et al (2019), the authors confirmed the existence of a positive relationship between attitudes and green purchase intentions and concluded that individuals believe that the behavioural intention of green consumption can protect their health. Shimul et al (2021) reported that consumers' environmental and natural green-product-related knowledge and information can lead to an increase in consumer positive attitudes and purchase of green products behavioural intention.…”
Section: H1mentioning
confidence: 99%
“…The sum of a person's feelings about himself or herself to serve as an object is referred to as self-image (Hershey & Wilson, 1997). Both female and male consumers use gender-specific skincare products to enhance their self-image (Grubb & Grathwohl, 1967;Shimul, Cheah, & Khan, 2022). Besides, body image is a part of self-image, and in many societies, it has become a critical component influencing people to tujom ( 2022) 7 ( 2):72-84 exercise and use skincare products (Sturrock & Pioch, 1998).…”
Section: Self-image (Si)mentioning
confidence: 99%